High throughput screening of inhibitors for tuberculosis at NCL : a novel drug discovery initiative from CSIR - Manek, Hardik; Nawale, Laxman; Jadhav, Nandadeep J.; Sarkar, Dhiman (73rd CSIR Foundation Day, at CSIR-National Chemical Laboratory, Pune, 2015)
Discover and develop novel drugs that are effective at curing latent, drug sensitive and drug resistant TB Study the biology of tuberculosis bacilli in great detail to identify new metabolic pathways that may be vulnerable to drugs Test thousands of potential drugs in our screening facility to find new compounds or new compound classes that kill TB bacteria Increase throughput up to 20,000 compounds at a time Develop novel screens using conditions that mimic those the TB bacteria encounters in the human body Utilize medical chemistry to optimize the structures of compounds so that they kill TB bacteria in a more potent fashion and are non-toxic Meet the challenges from industry